2020
DOI: 10.14814/phy2.14446
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model of reversible bile duct obstruction demonstrates rapid improvement of cholestatic liver injury

Abstract: There are limited murine models of cholestatic liver diseases characterized by chronic biliary obstruction and resumption of bile flow. While murine bile duct ligation (BDL) is a well‐established model of obstructive cholestasis, current models of BDL reversal (BDLR) alter biliary anatomy. We aimed to develop a more physiologic model of BDLR to evaluate the time course and mechanism for resolution of hepatic injury after biliary obstruction. In the present study, we restored bile flow into the duodenum without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Mice showed a comparable distorted liver architecture much later—after four weeks. The literature describes in part similar results predominantly for rats, whereas we found more studies with divergent results in mice [ 26 28 , 33 ]. The literature provides no explanation for the differences between the studies and species (see Table 6 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Mice showed a comparable distorted liver architecture much later—after four weeks. The literature describes in part similar results predominantly for rats, whereas we found more studies with divergent results in mice [ 26 28 , 33 ]. The literature provides no explanation for the differences between the studies and species (see Table 6 ).…”
Section: Discussionsupporting
confidence: 67%
“…In our study, no signs of surgical complication (e.g., bleeding, ischemia, biliary leakage), were identified during autopsy. Some authors concluded that mice are not suitable as animal model of biliary occlusion due the high perioperative mortality and the susceptibility to complications [ 2 , 3 , 26 , 28 ]. However, in the three mice dying spontaneously, the number of visible liver necroses was higher than in all other mice sacrificed at the designated time points.…”
Section: Discussionmentioning
confidence: 99%
“…The ALP value is related to whether the intrahepatic and extrahepatic bile ducts are blocked. The ALP value on the 7th day after ASAE was still significantly higher than that of the CK group, this is related to the fact that cholestasis caused by bile duct blockage does not self-adjust and recover in a short time ( Boyer, 2013 ; Taylor et al, 2020 ). The changes of pathological section and liver coefficient further indicated that liver morphological damage was difficult to recover spontaneously in a short time.…”
Section: Discussionmentioning
confidence: 89%
“…More specifically, studies in murine BDL have shown that macrophages contribute to both the progression and resolution of fibrosis in the setting of obstructive cholestasis 7 . In line with these studies, we previously established an innovative model of reversible BDL and demonstrated elevated hepatic CD68 in mice both after BDL alone, and after BDL with reversal and improved liver injury 8 . This prior work demonstrates the importance of determining both the subset-specific and stage-specific macrophage functions in cholestasis.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, we identified etiology-specific macrophage functions through comparison of neonatal BDL and murine BA. Future research will include validation studies of our macrophage subsets by histology, time point data, the inclusion of alternate neonatal models such as reversible models of BDL and the RRV reassortant-induced murine model of liver fibrosis, and comparison of our model to adult models to provide a deeper understanding of age-specific differences in the neonatal immune response to obstructive cholestasis 8 , 53 . Ultimately by translating findings from our novel neonatal model of BDL to children with cholestasis, we hope to identify disease-specific and macrophage subset-specific immunomodulatory therapies to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%